Motivasi dan Perilaku Konsumen dalam Keputusan Pembelian Produk Industri Kerajinan Kulit di Yogyakarta - Eny Sulistyowati (Jurnal Maksipreneur, 2013)
This study aims to determine the motivation and consumer behavior housewife and working woman in buying industri leather craft in Yogyakarta as well as to determine differences in motivation and behavior in both the consumer groups. By knowing the motivation and behavior of the consumer businesses industry leather craft can determine appropriate marketing strategy with the behavior of the market segment, so that could have an impact on the success of the business. From the results of recent research indicates that the information obtained by the two consumer groups are obtained from your friends as much as 52%, the rest of the other. Consumer behavior based on the influence in the purchase of leather, for the respondents indicate that employee that affect the purchase of craft leather 56% from friends, 19% from advertising, 17% from relation and 8% of the others. As for the housewife respondents shows that 32% of a friend, 32% of siblings, 24% from advertising and 12% from others. Consumer motivation in buying leather by the price factor of employee respondents showed a mean of 3.52 and respondents housewife at 3.53 which means it is very strong. Consumer motivation in buying leather craft design based on factors of employee respondents showed a mean 2.84 and respondents housewife at 3.11 which means strong. Consumer motivation in buying leather by the quality factor of employee respondents and respondents showed a mean of 2.68 by 2.82 housewife meaning strong. There is no difference between the consumer motivation housewife and employee.